Application of anionic surfactant as electrolyte for desorption of cesium by Prussian blue analogue electrochemical method
By using anionic surfactant as the electrolyte in the electrochemical decesilon of Prussian blue analogues, using its anion size greater than 1 nm and a larger electrochemical window, the problem of low desorption efficiency of Prussian blue analogues after adsorption of cesium is solved, and efficient desorption of cesium ions and recycling of electrodes is achieved.
Patent Information
- Application Number
- CN202411966654.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, after adsorbing cesium, the single desorption rate of Prussian blue analogues is low during the electrochemical desorption process and cannot be effectively recycled.
Anionic surfactants are used as electrolytes, such as sodium alkyl sulfate, sodium alkyl sulfate and sodium sulfate of fatty alcohols. As electrolytes in the electrochemical deces of Prussian blue analogues, the anion size greater than 1 nm and a larger electrochemical window are used to achieve efficient desorption of cesium ions.
The cesium ion desorption efficiency of Prussian blue analog electrochemical method was significantly improved to reach 90%, and the problems of low desorption voltage and low current efficiency were solved, achieving efficient desorption of cesium ions and recycling of electrodes.
Smart Images

Figure CN119753354A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of electrochemical adsorption separation of metal ions, and relates to electrochemical adsorption-desorption extraction of cesium ions in liquid cesium ore using a Prussian blue analogue as an electrode material, in particular to an electrolyte that is well matched with the Prussian blue analogue electrode material in the process of desorbing cesium. Background Art
[0002] Cesium and its compounds are widely used in microelectronics, medical treatment, petrochemicals, biopharmaceuticals and other fields due to their unique physical and chemical properties. In recent years, the demand has surged, resulting in a market supply shortage and a high price (about 70,000 yuan / kg). This highlights the importance of cesium resource mining and recycling. Although my country's solid cesium ore resources are limited, a large amount of cesium is contained in abundant salt lake brine, groundwater, etc. Therefore, it is of great significance to separate and extract cesium ions from these liquid cesium ores, which will help achieve the comprehensive development of liquid cesium ores and the sustainable development of the economy and society.
[0003] Electrochemical methods have become an ideal choice for separating cesium from liquid cesium ore due to their environmental friendliness, ease of operation, high efficiency and greenness. Prussian blue analogs are used in electrochemical cesium extraction processes due to their open ion channels, suitable lattice gaps and abundant redox active sites, which can effectively accommodate and reversibly extract alkali metal ions. They show excellent selectivity and stability. The general chemical formula of Prussian blue analogs is K x M[Fe(CN)6] 1-y □ y ·nH2O (M is a transition metal, □ is a lattice defect, 0≤x≤2, y<1). The main principle of electrochemical extraction of cesium using Prussian blue analogs as electrode materials is: under the action of DC voltage, the cathode material K x M[Fe 3+ (CN)6] 1-y Charging, Fe 3+ Gaining electrons and becoming Fe 2+ After that, in order to maintain the electrical neutrality of the electrode material, the cesium ions are forced into the lattice gap to achieve the insertion of cesium ions. The desorption process of cesium is based on the K x CsM[Fe 2+ (CN)6] 1-y As the anode, the desorption process of Fe 2+ Loses electrons to become Fe 3+ Finally, in order to maintain the electrical neutrality of the material, the cesium ions are released and enter the electrolyte to achieve the release of cesium ions. It can be seen that the efficient adsorption and desorption process of Prussian blue analogs on cesium is the key to selectively extracting cesium from liquid ore.
[0004] In recent years, the electrochemical extraction of cesium based on Prussian blue analogs has made significant progress. For example, Zhang et al. (Desalination, 2023, 549, 116331.) designed and prepared a nickel-based Prussian blue analog / porous carbon electrode. At a voltage of -3V, the maximum adsorption capacity of cesium was 155.2mg / g. Although Prussian blue analogs have achieved many results in the adsorption process of cesium, there are still many scientific and technological problems that need to be solved. In particular, after Prussian blue analogs adsorb cesium, their electrochemical desorption process often uses high-concentration inorganic salts such as KNO3, KCl and Na2SO4 as electrolytes, and the single desorption rate is low. For example, Kim et al. (Chemical Engineering Journal, 2022, 450, 138029) used 0.1M KNO3 as an electrolyte to investigate the desorption performance of zinc-based Prussian blue analog electrodes for cesium. The results showed that its single desorption rate was less than 55%. The copper-based Prussian blue analog synthesized by Tao et al. (Chemnanomat, 2015, 3, 188-193) has a cesium desorption rate of less than 30%, and the electrode cannot be regenerated.
[0005] Therefore, developing efficient desorption electrolytes to solve the problem that cesium ions cannot be effectively desorbed after adsorption has important theoretical and application significance. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an anionic surfactant used as an electrolyte to improve the efficiency of electrochemical desorption of cesium by a Prussian blue analogue, which can significantly improve the efficiency of electrochemical desorption of cesium by a Prussian blue analogue.
[0007] The anion size of the anionic surfactant of the present invention is larger than the lattice gap of the Prussian blue analog. In particular, when the anion size of alkyl sodium sulfonate, alkyl sodium sulfate and fatty alcohol sodium sulfate, which are larger than 1 nm, soluble in water and have a large electrochemical window, is used as the Prussian blue analog electrochemical decesium electrolyte, efficient desorption of cesium ions can be achieved at a lower voltage and high current efficiency.
[0008] Sodium alkyl sulfonate, sodium alkyl sulfate and sodium fatty alcohol sulfate play an important role in the fields of textile, leather, papermaking, food, petroleum, metal processing, mining and coal. However, it is rarely reported that they are used as electrolytes in the electrochemical desorption process of Prussian blue analogs after cesium adsorption.
[0009] Furthermore, the anionic surfactant is one of sodium hexadecyl diphenyl ether disulfonate (SHDDPED), sodium dodecyl diphenyl ether disulfonate (SDDD), sodium dodecyl sulfonate (SDS), sodium dodecyl benzene sulfonate (SDBS), and sodium fatty alcohol polyoxyethylene ether sulfate (APOES). Preferably, sodium hexadecyl diphenyl ether disulfonate.
[0010] Furthermore, the active component in the working electrode of the Prussian blue analogue electrochemical method for desorption of cesium is a cubic crystal of the Prussian blue analogue that has completely adsorbed cesium, and the transition metal contained therein may be Cu 2+ 、Zn 2+ , Mn 2+ 、Ni 2+ , Fe 2+ etc. Since Prussian blue analogues have similar cubic crystal structures with a lattice gap of less than 1 nm, Prussian blue analogues with different transition metals can achieve high desorption efficiency of cesium.
[0011] Furthermore, the anionic surfactant is used as an electrolyte with a concentration of 0.005-0.025 mol / L, preferably 0.02 mol / L.
[0012] Furthermore, the ratio of the volume of the anionic surfactant used as electrolyte to the mass of the Prussian blue analog in the working electrode is 30-60, preferably 50, L / g.
[0013] Furthermore, the working voltage of electrochemical desorption of cesium is 0.5V-1.2V, preferably 1V.
[0014] Furthermore, the electrochemical desorption time of cesium is 0.5h-2.5h, preferably 2h.
[0015] The mechanism of the anionic surfactant used as the electrolyte to achieve high-efficiency desorption of the Prussian blue analog after cesium adsorption is an enhanced decesium removal process based on the "size effect", that is, the minimum size of the anion in the surfactant is larger than the lattice gap of the Prussian blue analog, which not only avoids the anion from entering the Prussian blue analog to cause pore blockage and the inability to desorb the cesium ion, but also can be outside the lattice of the Prussian blue analog to react with Fe 3+ The electrostatic effect synergistically promotes the release of cesium ions, thereby achieving high-efficiency desorption of cesium ions.
[0016] Advantages and beneficial effects of the present invention:
[0017] (1) Based on the size effect, the present invention adopts for the first time anionic surfactants whose anion size is larger than the lattice gap of Prussian blue analogs as electrolytes in the electrochemical desorption process of cesium ions, and the desorption efficiency can reach up to 90%, thereby achieving efficient desorption of cesium ions.
[0018] (2) The anionic surfactant used in the present invention is a desorption electrolyte with low desorption voltage and high current efficiency, which effectively solves the problem of poor desorption performance and inability to recycle after cesium extraction from Prussian blue analogs.
[0019] (3) The anionic surfactant used in the present invention is a desorption electrolyte. The anion has a size greater than 1 nm and is universally applicable to Prussian blue analog electrodes. The desorption efficiency will not be reduced due to changes in the transition metal in the Prussian blue analog.
[0020] (4) Anionic surfactants with large-sized anions and wide electrochemical windows are inexpensive, non-volatile, and easy to separate. They can be widely used in the electrochemical desorption process of cesium using Prussian blue analogs as electrodes, truly realizing the electrochemical adsorption-desorption of cesium in liquid cesium ore. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The effect of different concentrations of sodium hexadecyl diphenyl ether disulfonate as the desorption electrolyte on the desorption efficiency in Example 1 of the present invention;
[0022] Figure 2 The effect of different transition metal species doped in the Prussian blue analog electrode material on the desorption efficiency in Example 2 of the present invention;
[0023] Figure 3 The effect of different desorption voltages on the desorption efficiency in Example 3 of the present invention;
[0024] Figure 4 The effect of different desorption times on the desorption efficiency in Example 4 of the present invention;
[0025] Figure 5 The effect of different types of anionic surfactants on the desorption efficiency in Example 5 of the present invention;
[0026] Figure 6 The transmission electron microscope image of the manganese-based Prussian blue analogue used in Example 6 of the present invention (left) and the ball-and-stick model of sodium hexadecyl diphenyl oxide disulfonate (right); DETAILED DESCRIPTION
[0027] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0028] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents described are commercially available unless otherwise specified.
[0029] Embodiment 1:
[0030] Using sodium hexadecyl diphenyl oxide disulfonate in anionic surfactant as desorption electrolyte, manganese-based Prussian blue analog electrode material after cesium adsorption as working electrode, platinum mesh and Ag / AgCl (saturated KCl) electrode as counter electrode and reference electrode respectively, electrochemical desorption experiment was carried out to investigate the effect of different concentrations of sodium hexadecyl diphenyl oxide disulfonate on desorption efficiency, including the following steps:
[0031] (1) preparing aqueous solutions of sodium hexadecyl diphenyl ether disulfonate with molar concentrations of 0.005 mol / L, 0.01 mol / L, 0.015 mol / L, 0.02 mol / L and 0.025 mol / L as desorption electrolytes;
[0032] (2) A manganese-based Prussian blue analogue with a cesium adsorption capacity of 310 mg / g was used as the active component of the working electrode, 0.001 g of the effective active component was added with a conductive agent multi-walled carbon nanotube (the mass ratio of manganese-based Prussian blue analogue to multi-walled carbon nanotube was 8:2), a binder perfluorinated resin solution and a dispersant acetone (the volume ratio of the perfluorinated resin solution to acetone was 0.05:1) to prepare a working electrode;
[0033] (3) The desorption voltage was 1 V, the desorption time was 2 h, and 50 mL of sodium hexadecyl diphenyl ether disulfonate aqueous solution with different molar concentrations was used as the desorption electrolyte for electrochemical desorption experiments;
[0034] (4) The cesium ion concentration in the electrolyte solution after electrochemical desorption was determined using inductively coupled plasma optical emission spectroscopy (ICP-OES) and the desorption efficiency was calculated, such as Figure 1 As shown in the figure, under the same electrochemical desorption time, as the concentration of sodium hexadecyl diphenyl oxide disulfonate in the desorption electrolyte increases, the desorption efficiency increases. When the concentration of sodium hexadecyl diphenyl oxide disulfonate increases to 0.02 mol / L, the desorption efficiency no longer changes. Therefore, a desorption electrolyte concentration of 0.02 mol / L can achieve efficient desorption of cesium ions.
[0035] Embodiment 2:
[0036] Using sodium hexadecyl diphenyl ether disulfonate as the desorption electrolyte, using a platinum mesh and an Ag / AgCl (saturated KCl) electrode as the counter electrode and the reference electrode, respectively, and using a manganese-based Prussian blue analog electrode material, a zinc-based Prussian blue analog electrode material, and a copper-based Prussian blue analog electrode material after adsorbing cesium as working electrodes, an electrochemical desorption experiment was carried out to investigate the effect of the type of transition metal doped in the Prussian blue analog on the desorption efficiency, including the following steps:
[0037] (1) preparing working electrodes using a manganese-based Prussian blue analogue, a zinc-based Prussian blue analogue and a copper-based Prussian blue analogue with an effective active component mass of 0.001 g and a cesium adsorption capacity of about 310 mg / g as working electrode active components;
[0038] (2) An electrochemical desorption experiment was performed at a desorption voltage of 1 V and a desorption time of 2 h using 50 mL of 0.02 mol / L sodium hexadecyl diphenyl ether disulfonate as the desorption electrolyte;
[0039] (3) Use ICP-OES to measure the cesium ion concentration in the electrolyte solution after electrochemical desorption and calculate the desorption efficiency, such as Figure 2 As shown, under the same experimental conditions, changing the type of transition metal in the Prussian blue analogue has little effect on the desorption efficiency, which proves that the sodium hexadecyl diphenyl ether disulfonate desorption electrolyte is universal.
[0040] Embodiment 3:
[0041] Using sodium hexadecyl diphenyl ether disulfonate in anionic surfactant as desorption electrolyte, manganese-based Prussian blue analog electrode material after cesium adsorption as working electrode, platinum mesh and Ag / AgCl (saturated KCl) electrode as counter electrode and reference electrode respectively, electrochemical desorption experiment was carried out to investigate the effect of different desorption voltages on desorption efficiency, including the following steps:
[0042] (1) preparing a working electrode using a manganese-based Prussian blue analogue with an effective active component mass of 0.001 g and a cesium adsorption capacity of 310 mg / g as the working electrode active component;
[0043] (2) Using 50 mL, 0.02 mol / L sodium hexadecyl diphenyl ether disulfonate as the desorption electrolyte, the desorption time was 2 h, and the electrochemical desorption experiment was carried out at desorption voltages of 0.5 V, 0.6 V, 0.7 V, 0.8 V, 0.9 V, 1 V, 1.1 V, and 1.2 V;
[0044] (3) Use ICP-OES to measure the cesium ion concentration in the electrolyte solution after electrochemical desorption and calculate the desorption efficiency, such as Figure 3 As shown in the figure, under the same experimental conditions, with the increase of desorption voltage, the desorption efficiency gradually increases. When the desorption voltage reaches 1V, the desorption efficiency no longer changes. Therefore, a desorption voltage of 1V can achieve efficient desorption of cesium ions.
[0045] Embodiment 4:
[0046] Using sodium hexadecyl diphenyl ether disulfonate in anionic surfactant as desorption electrolyte, manganese-based Prussian blue analog electrode material after cesium adsorption as working electrode, platinum mesh and Ag / AgCl (saturated KCl) electrode as counter electrode and reference electrode respectively, electrochemical desorption experiment was carried out to investigate the effect of different desorption time on desorption efficiency, including the following steps:
[0047] (1) preparing a working electrode using a manganese-based Prussian blue analogue with an effective active component mass of 0.001 g and a cesium adsorption capacity of 310 mg / g as the working electrode active component;
[0048] (2) Electrochemical desorption experiments were conducted with 50 mL, 0.02 mol / L sodium hexadecyl diphenyl oxide disulfonate as the desorption electrolyte and a desorption voltage of 1 V at desorption times of 0.5 h, 1 h, 1.5 h, 2 h, and 2.5 h, respectively;
[0049] (3) Use ICP-OES to measure the cesium ion concentration in the electrolyte solution after electrochemical desorption and calculate the desorption efficiency, such as Figure 4 As shown in the figure, under the same experimental conditions, with the increase of desorption time, the desorption efficiency gradually increases. When the desorption time reaches 2h, the desorption efficiency no longer changes. Therefore, a desorption time of 2h can achieve efficient desorption of cesium ions.
[0050] Embodiment 5:
[0051] Using different types of anionic surfactants as desorption electrolytes, manganese-based Prussian blue analog electrode materials after cesium adsorption as working electrodes, platinum mesh and Ag / AgCl (saturated KCl) electrodes as counter electrodes and reference electrodes, respectively, electrochemical desorption experiments were carried out to investigate the effects of different anionic surfactants as desorption electrolytes on the desorption efficiency, including the following steps:
[0052] (1) preparing aqueous solutions of sodium hexadecyl diphenyl ether disulfonate, sodium dodecyl diphenyl ether disulfonate, sodium dodecyl sulfonate, sodium dodecyl benzene sulfonate, and sodium fatty alcohol polyoxyethylene ether sulfate with a concentration of 0.02 mol / L respectively as desorption electrolytes;
[0053] (2) preparing a working electrode using a manganese-based Prussian blue analogue with an effective active component mass of 0.001 g and a cesium adsorption capacity of 310 mg / g as the working electrode active component;
[0054] (3) The electrochemical desorption experiment was carried out with a desorption voltage of 1 V, a desorption time of 2 h, and 50 mL of 0.02 mol / L aqueous solutions of different anionic surfactants as desorption electrolytes;
[0055] (4) Use ICP-OES to measure the cesium ion concentration in the electrolyte solution after electrochemical desorption and calculate the desorption efficiency, such as Figure 5 As shown, under the same experimental conditions, surfactants with larger anion sizes can achieve efficient desorption of cesium, among which sodium hexadecyl diphenyl ether disulfonate has the best effect.
[0056] Embodiment 6:
[0057] Desorption mechanism study
[0058] First, 1.0M KCl was used as the electrolyte to investigate its electrochemical decesium performance on the manganese-based Prussian blue analog after cesium adsorption. The results showed that its desorption rate for cesium ions was only 32%. The results of X-ray diffraction and transmission electron microscopy analysis showed that the desorbed material had a stable crystal structure, but chlorine was detected in the desorbed manganese-based Prussian blue analog. This result indicates that during the electrochemical decesium process, a large number of chloride ions around the anode entered the lattice gap of the manganese-based Prussian blue analog, neutralizing the positive charge of the material and preventing the cesium ions from escaping. Therefore, how to prevent anions from entering the lattice gap of the Prussian blue analog during the desorption process is the key to improving the desorption rate.
[0059] Combined with transmission electron microscopy, it can be seen that the maximum lattice gap of the synthesized Prussian blue analogue cubic crystal is less than 1nm. Theoretical calculations show that the minimum size of the anion in the surfactant sodium hexadecyl diphenyl ether disulfonate is 1.234nm, which is larger than the lattice gap of the Prussian blue analogue. 3+ The electrostatic interaction promotes the cesium ion release ( Figure 6 ). This is the mechanism of enhancing cesium removal based on the anion "size effect".
[0060] The above shows and describes the implementation examples of the present invention, or the technical solutions of the accompanying drawings, which all embody a class of electrolytes for realizing efficient decesium of Prussian blue analogs based on size effect of the present invention. It should be understood that for those skilled in the art, improvements or changes can be made according to the above description, and all these improvements and changes should belong to the protection scope of the claims attached to the present invention.
Claims
1. Application of an anionic surfactant as an electrolyte for electrochemical desorption of cesium from a Prussian blue analog, characterized in that: The anion size of the anionic surfactant is larger than the lattice gap of the Prussian blue analog.
2. The use according to claim 1, characterized in that: The anionic surfactant is sodium alkyl sulfonate, sodium alkyl sulfate and sodium fatty alcohol sulfate.
3. The use according to claim 2, characterized in that: The anionic surfactant is one of sodium hexadecyl diphenyl ether disulfonate, sodium dodecyl diphenyl ether disulfonate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate and sodium fatty alcohol polyoxyethylene ether sulfate.
4. The use according to claim 1, characterized in that: The anionic surfactant is used as electrolyte with a concentration of 0.005-0.025 mol / L.
5. The use according to claim 1, characterized in that: The active component of the working electrode in the electrochemical desorption of cesium by the Prussian blue analogue is a cubic crystal of the Prussian blue analogue that has completely adsorbed cesium, and the transition metal contained in the cubic crystal is Cu. 2+ 、Zn 2+ , Mn 2+ 、Ni 2+ or Fe 2+ .
6. The use according to claim 5, characterized in that: The anionic surfactant is used as electrolyte, and the ratio of its volume to the mass of the Prussian blue analogue in the working electrode is 30-60 (L / g).
7. The use according to claim 1, characterized in that: The working voltage of electrochemical desorption of cesium is 0.5V-1.2V.
8. The use according to claim 1, characterized in that: The electrochemical desorption time of cesium is 0.5h-2.5h.